ANALISIS PENILAIAN AUTENTIK PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTs. NURUL IKHLAS PINTU GOBANG KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Zahrah Zettiara; Zulhaini Zulhaini; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2020)
This research is motivated by the emergence of curriculum changes to 2013 curriculum which seeks to improve assessment standards, namely authentic assessment. This assessment is based on data that reflects the ability of students, namely assessmentsthat are based on the learning process not just the results. This assessment also focuses on three domains, that is knowledge, skills and attitudes. Differ from the previous assessment which only focuses on knowledge aspects.This research aims to knuw theprocess of carrying out authentic assessment in the subjects of Aqeedah Akhlak VIII grade at MTs. Nurul Ikhlas Pintu Gobang Kari. This type of research used in this study is a qualitative descriptive field research. Regarding the Analysis of Authentic Assessmentsin the Subjects of Aqeedah Akhlak in Class VIII at MTs. Nurul Ikhlas Pintu Gobang Kari, Kuantan Tengah District, Kuantan Singingi Regency. Data collection is taken by observation, interview and documentation. Data collection techniques using data analysis according to Miles and Huberman. With the flow stages: data collection, data reduction, data presentation and conclusions. Research results: (1) In the Learning Implementation Plan (RPP) includes preliminary activities, core activities, and closing activities. (2) Authentic assessment is carried out before the learning process, during the learning process, and after the learning takes place. (3) Analysis of the results of the assessment, conducted by the teacher to find out how successfully students master the material that has been submitted by the teacher.